Implementasi Teknik Granulasi Serbuk Jamu untuk Optimalisasi Proses Produksi Pabrik Jamu Suti Sejati - Ahmad Ainurofiq; Syaiful Choiri; Dinar Sari Cahyaningrum Wahyuni; Saptono Hadi; Rita Rakhmawati; Nestri Handayani; Estu Retnaningtyas Nugraheni; Muhammad Adam Firdausi (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
The process of making herbal powder needs to be optimized because it is not efficient, and the filling process is still manually into teabags. The purpose of empowerment is to increase the effectiveness and efficiency of the herbal medicine-making process through a pharmaceutical approach with granulation techniques. This service is based on data obtained quantitatively in the laboratory, including the characteristics of the size distribution of Simplicia powder and granules and the flowability of herbal medicine powders. The data obtained were analyzed statistically with a 95% confidence level (p=0.05). The results showed that the granulation technique increased the flowability of the herbal powder with a flowability of 0 to 11.94±0.54 g/second. The granulation technique is able to improve the process of extracting herbs during brewing. The success of this activity is measured through the technique of increasing the flowability of herbal powders and the use of automatic teabag fillers. The results of the program showed that the granulation technique was able to increase the efficiency of the herbal powder manufacturing process at the Suti Sehati Herbal Medicine Factory, Sukoharjo.